Population cycles and outbreaks of small rodents: ten essential questions we still need to solve - Andreassen, Harry P.; Sundell, Janne; Ecke, Fraucke; Halle, Stefan; Haapakoski, Marko; Henttonen, Heikki; Huitu, Otso; Jacob, Jens; Johnsen, Kaja; Koskela, Esa; Luque-Larena, Juan Jose; Lecomte, Nicolas; et al. (Springer, 2021)
Most small rodent populations in the world have fascinating population dynamics. In the northern hemisphere, voles and lemmings tend to show population cycles with regular fluctuations in numbers. In the southern hemisphere, small rodents tend to have large amplitude outbreaks with less regular intervals. In the light of vast research and debate over almost a century, we here discuss the driving forces of these different rodent population dynamics. We highlight ten questions directly related to the various characteristics of relevant populations and ecosystems that still need to be answered. This overview is not intended as a complete list of questions but rather focuses on the most important issues that are essential for understanding the generality of small rodent population dynamics.